2014
DOI: 10.1371/journal.pone.0105479
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Dimerization Is Regulated by Heat Shock Protein 90 Rather than by Phosphorylation

Abstract: Endothelial nitric oxide synthase (eNOS) is a multifunctional enzyme with roles in diverse cellular processes including angiogenesis, tissue remodeling, and the maintenance of vascular tone. Monomeric and dimeric forms of eNOS exist in various tissues. The dimeric form of eNOS is considered the active form and the monomeric form is considered inactive. The activity of eNOS is also regulated by many other mechanisms, including amino acid phosphorylation and interactions with other proteins. However, the precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…4 Recent evidence also demonstrated that Ser1179 phosphorylation exclusively exists in eNOS dimer at both resting and stimulated condition. 5 As shown in Figure 4a, our results demonstrated a significant downregulation of both total and phospho eNOS expression in Ins2…”
Section: Expression Of Total Versus Phospho Enos and Endothelial Nos supporting
confidence: 60%
See 2 more Smart Citations
“…4 Recent evidence also demonstrated that Ser1179 phosphorylation exclusively exists in eNOS dimer at both resting and stimulated condition. 5 As shown in Figure 4a, our results demonstrated a significant downregulation of both total and phospho eNOS expression in Ins2…”
Section: Expression Of Total Versus Phospho Enos and Endothelial Nos supporting
confidence: 60%
“…3 In vitro studies from our laboratory and reports from other investigators have shown that the regulation of eNOS activity is mediated by heat shock protein-90 (Hsp-90). 4,5 The interaction of eNOS with Hsp-90 favors the phosphorylation of eNOS at Ser1177 by Akt kinase. This phosphorylation process is a key event which augments eNOS activity leading to NO production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction increases calmodulin binding, thus sensitizing the system to rises in calcium levels [58]. Recent work has shown that hsp90 is required for dimerization, and it is this dimerization that is the predominant condition for eNOS phosphorylation and activation rather than the modifications being the permissive event for dimerization [59]. Hsp90 promotes these phosphorylation events by potentially increasing the binding affinity for eNOS and Akt and causing a conformational shift that unmasks sites for modification [60, 61].…”
Section: Regulation Of No Production: the Dynamic Modulation Of Enosmentioning
confidence: 99%
“…The expressed wild-type eNOS and S1179D eNOS proteins were harvested and purified according to the description of previous publications [17] [11]. …”
Section: Methodsmentioning
confidence: 99%